Financial burden among cancer patients: A national‐level perspective. (19th July 2022) - Mudaranthakam, Dinesh Pal; Wick, Jo; Calhoun, Elizabeth; Gurley, Tami
Abstract: Background: This research study aimed to evaluate the financial burden among older cancer patients and its corresponding risk factors. Factors such as increasing treatment costs and work limitations often lead cancer patients to bankruptcy and poor quality of life. These consequences, in turn, can cause higher mortality rates among these patients. Methods: This retrospective cohort study utilized data from the Health Retirement Study (HRS), conducted by the University of Michigan ( N  = 18, 109). Eligible participants had responses captured from years 2002 to 2016. Participants were classified according to any self‐reported cancer diagnosis (yes or no) and were compared on the basis of financial, work, and health‐related outcomes. Propensity score (PS) matching was applied to reduce the effects of potential confounding factors. Also only, individuals with an age ≥50 and ≤85 during Wave 6 were retained. Results: Multivariate analysis with random effects revealed several indicators of financial burden when comparing participants with a cancer diagnosis to those with no history of cancer. Mean out‐of‐pocket costs associated with a cancer diagnosis were $1058 higher when compared to participants with no history of cancer, suggesting that even cancer patients with insurance coverage faced out‐of‐pocket costs. Respondents with cancer patients had higher odds of encountering financial hardship if they are facing Work Limitations (OR = 2.714), Regular use of Medications (OR = 2.518), Hospital Stays (OR = 2.858), Declining Health (OR = 2.349), or were being covered under government health insurance (OR = 5.803) than respondents who did not have cancer, or suffered from mental health issues such as Depression (OR = 0.901). Conclusion: Cancer patients contend with increasing financial costs during their treatment. However, most newly diagnosed patients are not aware of these costs and are given few resources to handle them. Abstract : Given that this study cohort is primarily senior citizens, it is especially troubling that an active working status seems to be an important requirement for managing cancer treatment without severe financial hardship. In the absence of more robust financial support for these patients, financial planning has become a vital part of the treatment process for cancer patients. Until the introduction of legislation that makes cancer treatment financially viable, health systems have a responsibility to direct resources toward the education and assistance of these patients.